Cross-country analysis of correlation between protection of women's economic and social rights, health improvement and sustainabledevelopment. Issue 6 (18th July 2019) - Alaei, Kamiar; Akgüngör, Sedef; Chao, Weng-Fong; Hasan, Sayyida; Marshall, Allyson; Schultz, Emily; Alaei, Arash
Abstract : Objective: The goal of this study is to assess the correlation between protection of women's economic and social rights (WESR), health improvement and sustainable development. Methods: A cross-country analysis of 162 countries was employed to assess development, health and human rights of the countries by measuring associated variables. Data sets for the health, human rights and economic and social rights of these countries were from 2004 to 2010. The dependent variables are health and human development and the independent variables are the human rights variables. Regression analysis and principle axis factoring were used for extraction and varimax method for rotation. Country grouping was made using cluster analysis. Potential biases, resulting from measurement differences in human rights values, were eliminated by using z-transformation to standardise variables. Results: Regression results reveal that WESR variable is correlated with the health outcomes. Cluster analysis separated the countries into three clusters, based on the WESR variable. Countries where WESR were 'highly respected' (44 countries) are categorised into cluster 1; countries where WESR were 'moderately respected' (51 countries) are categorised into cluster 2 and countries where WESR were 'poorly respected' (63 countries) are categorised into cluster 3. Countries were then compared in their respective clusters based on health and human development variables. It was found that the countries which 'highly respected' WESR had better average health values compared with the second and third clusters. Our findings demonstrate that countries with a strong women's rights status ultimately had better health outcomes. Conclusion: WESR status has correlation with the health and human development. When women's rights are highly respected, the nation is more likely to have higher health averages and accelerated development.